ANTIBIOGRAM AND MOLECULAR CHARACTERIZATION OF VIBRIO CHOLERAE ISOLATED FROM MARINE FISH - Angelo, Rwarinda U; Ramesh, Samiraj Ramesh (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: Molecular identification and antibiotic susceptibility evaluation of Vibrio cholerae from marine fish available in local fish market Thanjavur, Tamil nadu, India. Methods:Â inoculation was done by using nutrient agar as general media and TCBS agar as selective media and confirmed as V.cholerae by Gram stain (Microscopic Observation), Growth characteristics of different media, Biochemical tests like Methyl Red Test, Nitrate Reduction Tests, Indole Test etc. Sensitivity (drug sensitivity) was done in Muller Hinton Agar (MH Agar) using disc diffusion method ten different antibiotics were used to evaluate the antibiogram profile, molecular detection was done by targeting 16S rRNA gene by using a universal primer. Results:Â V.cholerae is present in marine fish samples, as showed by culture method and microscopic observation as well biochemical tests. PCR amplification of 16S rRNA gene showed the amplification of targeted gene and antibiogram profile showed that isolates are more sensitive to Ampicillin in comparison with others antibiotics used in this study. Ampicillin can be used for V.cholerae infection by the physicians and amoxicillin must be avoided which is resistant. Conclusion:Â Molecular detection is safe and rapid methods for bacteria identification as revealed by PCR amplification of 16S rRNA gene. As the isolates are more sensitive to Ampicillin in comparison with others antibiotics used in this study. Ampicillin can be used for V.cholerae infection by the physicians and amoxicillin and nitrofurantoin must be avoided. Â Â Â Â Â